The Venice Charter – between protection and socially useful purpose. - Iuliia Eremenko; Tymoteusz Kraski (Ochrona Dziedzictwa Kulturowego, 2024)
The principles of the Venice Charter are still invoked worldwide as a crucial reference point in discussions and practices related to heritage preservation. However, the Charter’s lack of clarity in defining stakeholders and procedural steps raises significant issues about who has the authority to determine the appropriateness of new functions for monuments. This deficiency can lead to decision-making that might not fully consider the diverse cultural values and historical significance of the sites, potentially resulting in conservation outcomes that are more economically than socially driven. This paper examines how national and international conservation policies have expanded upon the Venice Charter to address social participation and the concept of "socially useful purposes" in World Heritage site management. Focusing on Germany and Poland World Heritage cities, the study explores how national and international guidelines have expanded upon the Venice Charter to incorporate social participation and the concept of "socially useful purposes" in the management of World Heritage sites. It delves into the role of Site Management Plans as dynamic documents that have evolved from strict preservation frameworks to policies encompassing social participation, thereby enhancing community engagement and meeting a broader spectrum of conservation needs and stakeholder interests.